Have mobile devices changed working patterns in the 21st century? A time-diary analysis of work extension in the UK - Mullan, K; Wajcman, J (SAGE Publications, 2017)
It is commonly claimed that ubiquitous connectivity erodes the boundaries that once separated work from other aspects of life. Mobile devices in particular enable people to perform work-related activities anytime anywhere. Surprisingly, however, we know little about how people nationwide organise their daily working time over a period that has witnessed rapid technological change. Using the United Kingdom Time-Use Surveys 2000 and 2015, covering this period of technological change, we studied work extension practices, and the links between work extension, total work hours, and subjective time pressure. We found a significant, though small, increase in work extension, and evidence that it was significantly associated with time pressure in 2015, but not in 2000. Additionally, work extension increased total work time, which was concentrated entirely in time working with a mobile device. We discuss our results in light of some taken-for-granted narratives about mobile devices allowing work to colonise life.